The Influence of Brand Equity, Product Quality, And Promotion on Skin Care Product Purchase Decisions Among Teenagers at Unniqestore - Rahmawati, Noviana Anis; Huda, Nurul (Jurnal Ekuilnomi, 2026)
The rapid development of the cosmetics industry in Indonesia has increased the potential of the skincare market and influenced consumers lifestyles. In making purchasing decisions, consumers consider functional and psychological aspects, as well as external factors such as brand equity, product quality, and promotion. This study aims to analyze the influence of these three variables on purchasing decisions for skincare products at Unniqestore. The study used a quantitative method with 96 respondents selected through purposive sampling using the Rao Purba formula and analyzed using multiple linear regression with SmartPLS 4. The results showed that Brand Equity and Product Quality had a positive and significant effect on Purchase Decision, with Product Quality being the most dominant factor with the highest path coefficient (0.503). However, the Promotion variable has a small positive path coefficient (0.105) and was found to have no significant effect on Purchase Decision (P-value 0.259). Simultaneously, the three variables were able to explain 74.8% of the variation in Purchase Decision. These findings provide a basis for Unniqestore to prioritize brand strengthening and product quality assurance as key drivers, while reevaluating more effective promotional strategies